The contributionof pharmaceutical establishments in the prevention and managementof STD : a qualitative research in a city in southern Brazil - Rosso Neto, Camila; Galato, Dayani (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: sexually transmitted diseases (SDT) are presented as quite prevalent health problems which have implications on public health. Objective:a case study was conducted in order to describe the contribution of pharmaceutical establishments in the prevention and management of STD. Methods:the focus of this qualitative research was semi-structured interviews with individuals which were responsible for the dispensation of medicines in 20 pharmaceutical establishments in the city of Tubarão/SC in 2009. Results: it was possible to identify that pharmacy establishments assume various roles in the context of STD, which include being a gateway for healthcare services; venue for condom sales; guidance for the implementation of preventive examination; diagnostic assessment by signs and symptoms; self-medication with or without orientation; and prevention. Was Identified the use of emergency contraception by younger individuals was identified, thus performing only primary prevention of pregnancy, not STD. Another point is that little prevention is accomplished by pharmacy establishments even though they are characterized by being a prevention-oriented environment. Conclusion: the pharmacies contribute mainly to the management of STD through self-medication, and the actions related to prevention of these diseases are still very few.